Functional Role of Feed Enzymes in Broiler Diets: A Pathway to Enhanced Nutrient Utilization, Performance, Health and Welfare - Md. Emran Hossain (International Journal of Biochemistry and Biomolecule Research, 2025)
The inclusion of feed enzymes in broiler diets has emerged as a pivotal strategy for improving nutrient utilization, enhancing growth performance, and promoting overall health and welfare in modern poultry production. Feed enzymes, such as phytase, xylanase, and protease, facilitate the breakdown of complex molecules in feed ingredients, leading to increased bioavailability of essential nutrients and improved digestion efficiency. This review explores the underlying mechanisms by which feed enzymes contribute to enhanced nutrient absorption, focusing on their role in mitigating anti-nutritional factors and improving gut health. Additionally, the impact of enzyme supplementation on broiler performance, including weight gain, feed conversion ratio, and carcass quality, is examined in various production contexts. The influence of feed enzymes on animal welfare is also considered, particularly in relation to gut barrier function, immune response, and resilience to environmental stressors. By integrating scientific advancements with practical feeding strategies, this study highlights the potential of feed enzymes to optimize both productivity and welfare in broiler systems, while also contributing to more sustainable poultry production.
Keywords: Broiler Diets; Feed Enzymes; Nutrient; Proteases; biological catalysts